A wonderful year - Bruel, Nick. (New York : Roaring Brook Press, 2015)
"A picture book comically following one girl through each of the four seasons"--
"A Neal Porter Book."
Keywords: Seasons -- Fiction; Year -- Fiction; Humorous stories; JUVENILE FICTION / Concepts / Seasons; JUVENILE FICTION / Humorous Stories